Moment‐specific compliance with hand hygiene. (June 2014) - Lau, Tiffany; Tang, Grace; Mak, Ka‐lun; Leung, Gilberto
Summary Background Hand hygiene is an important component of patient‐safety education. The World Health Organization recommends the use of hand hygiene measures at five clinical moments. While previous studies have treated hand hygiene as a single entity, we investigated whether and how the compliance of students may vary across the five clinical moments. We also studied their reasons for non‐compliance with a view to inform teaching. Method A voluntary self‐administered questionnaire survey was conducted on a convenient sample of 339 medical and nursing students. The five clinical moments studied were: before touching a patient (moment 1); before a clean/aseptic procedure (moment 2); after body fluid exposure risk (moment 3); after touching a patient (moment 4); and after touching the patient's surroundings (moment 5). Results The overall reported compliance rate was 83.0 per cent. The compliance rates were significantly lower at moments 1 and 5. Nursing students reported better overall compliance (p = 0.01), and at moments 2 (p = 0.0001) and 3 (p = 0.0001), than medical students. Medical students fared better at moment 4 (p = 0.009). The most common reason reported for non‐compliance was 'forgetfulness'. Discussion We identified differences in compliance rates across the five clinical moments of hand hygiene. Education programmes should not treat the hand hygiene process as a single entity, but should adopt a moment‐specific approach to promote recall, with particular emphases on moments 1 and 5. Nursing and medical students may require different education strategies. Future studies on hand hygiene may also adopt a moment‐specific approach.